MASTER CRAFTSMAN COMBINING EMOTIONS AND LEARNING - Claudia Maritza Páez Jiménez; Judith Stella Páez Jiménez (LÍNEA IMAGINARIA, 2025)
This essay will explore the correlation between pedagogical practice and the emotional qualities of educators, based on the "master craftsman" model popularized by Richard Sennett. It will explain why excellence in teaching is an art in which reflection and commitment to the student’s holistic well-being are key to fostering quality education. Teaching practice is a dynamic process of planning, intention, and adjustment, a concept Donald Schön addresses through "reflection-in-action" and "reflection-on-action." The master craftsman teacher is reflective and does not merely apply pre-established techniques but rather analyzes and adapts their practice to the needs of the context. In this sense, the teacher becomes a guide for the holistic development of students, including their emotional dimension. For this reason, continuous professional development enables teachers to refine their "craft," contributing to forming well-rounded, resilient citizens capable of building positive interpersonal relationships. Additionally, the essay will address the characteristics of the “best teachers,” as proposed by Ken Bain, emphasizing the importance of respect for students, recognizing their humanity, diverse needs, and behaviors, and the necessity of creating challenging learning environments that foster confidence and motivation for meaningful learning. The master craftsman teacher encourages critical thinking, questioning the world, and developing their own potential by balancing knowledge and emotions in parallel. The figure of the master craftsman highlights the complexity of teaching. Just like an artisan who works with dedication and precision, the teacher is committed to "molding" their unique work, using knowledge, skills, and expertise to guide students. The master craftsman values the raw material they work with (the students), recognizes their individual traits, and strives to create a high-quality product: meaningful learning.